Implementasi Dukungan Teknologi terhadap Efektivitas Pembelajaran dalam Kurikulum Merdeka di SMKS Al Ittihad Cianjur - M Khoerudin; Dety Mulyanti (CV. ITTC INDONESIA, 2025)
This study explores the implementation of technological support in enhancing learning effectiveness under the Merdeka Curriculum at SMKS Al Ittihad Cianjur. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observations, and documentation. The study examines school policies, teacher practices, the effectiveness of technology use, and the factors that support or hinder its implementation. The findings reveal that the school provides comprehensive technological support, including internet infrastructure, digital teaching tools, and the use of the Pijarsekolah.id platform. This platform offers question banks, instructional videos, interactive e-books, and a digital assessment system. School leadership actively promotes the integration of these tools, supported by the vice principal for curriculum and technical staff. Teachers across different vocational departments apply technology creatively and adaptively. They report increased student engagement, improved assessment efficiency, and more personalized learning experiences. However, challenges remain, particularly in digital literacy disparities, inconsistent internet access, and varying levels of student readiness. In conclusion, technological support at SMKS Al Ittihad Cianjur plays a critical role in implementing the Merdeka Curriculum. Its success is influenced by strong leadership, teacher competence, and sustained technical assistance.